Балансы международной инвестиционной деятельности РФ (Путеводитель предпринимателя)
As the tool of the analysis of the international investment activity of the Russian Federation in article are considered a number of balances in which incomes from international (foreign and foreign) investments (reflected in section of the balance of payments «Account of current operations» would be considered).